Two new species of Arthoniaceae from old-growth European forests, Arthonia thoriana and Inoderma sorediatum, and a new genus for Schismatomma niveum. (19th March 2018) - ERTZ, Damien; SANDERSON, Neil; ŁUBEK, Anna; KUKWA, Martin
Abstract: Two new species of Arthoniaceae are described from old-growth European forests: Arthonia thoriana from Horner Combe in Great Britain and Inoderma sorediatum from the Białowieża Forest in Poland. Phylogenetic analyses using mtSSU sequences were used to determine the generic affiliation of the two species. Arthonia thoriana is characterized by a non-lichenized white thallus, pallid brown, white pruinose ascomata of 0·12–0·30 mm diam., richly anastomosing paraphysoids and (1–2–)3-septate ascospores of 9–12×3·0–3·5 µm. Inoderma sorediatum differs from all other species of the genus by a sorediate thallus and the production of confluentic acid. It is the sister species to I. afromontanum in our phylogenetic analyses. The discovery of the new species supports the high value of these forests for biodiversity action plans. Phylogenetic analyses also place Schismatomma niveum in the Arthoniaceae and the new genus Snippocia is described to accommodate it. The genus Leprantha is resurrected for its type species ( L. cinereopruinosa ). A lectotype is designated for Arthonia pruinosella .